Centesimus Annus and Lessons for Modern Organizational Leadership - Markey, Joseph (Lumen et Vita, 2024)
Since the issuance of the papal encyclical Rerum Novarum by Pope Leo XIII in 1891, Catholic social teaching has delivered a rich means of addressing the ever-changing economic and social landscape by offering timeless and consistent directives to tackle the current issues and challenges of the times. Many view Centesimus Annus, issued by John Paul II in 1991 to mark the 100th anniversary of Rerum Novarum, as a capstone of the numerous Catholic social teaching encyclicals that came before it. There is a body of research indicating that the faith traditions of leaders don’t explicitly or knowingly translate into how leaders behave and make decisions. More importantly, the character traits of many great leaders reflect core moral and ethical principles of the world’s major faith traditions, whether acknowledged by individual leaders or not. This understanding can lead to greater interest by leaders in the intersection of leadership and faith traditions. Citing relevant business case studies, this paper explores some of the indicative and imperative elements of Catholic social teaching, as reflected particularly in Centesimus Annus, and their applications for organizational leadership. At the core, is a recognition that many of the mandates embedded in Catholic social teaching embody what it means to be truly human, and are consistent with what modern leadership science studies consistently consider character traits of great leaders. Concepts include human dignity, subsidiarity, the greater good, stakeholder capitalism, and change management. Other concepts include Bernard Lonergan's perspective on general revelation emphasizing the importance of human cognition, and authenticity as a mark of great leaders.